TUJUAN DAN MANFAAT MEMPELAJARI PENDEKATAN SISTEM DALAM MANAJEMEN PENDIDIKAN - Ana Khoiriyah; Anis Azmiatu Silvia; Romlah; Saiful Anwar; Dwi Aprianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to examine the objectives and benefits of studying the systems approach in educational management. The systems approach is used to understand how various components in the education system, such as students, teachers, curriculum, and facilities, are interrelated and influence each other. The main objective of this approach is to improve the effectiveness of education management through comprehensive analysis, so that it can produce more appropriate policies and sustainable solutions. The benefits of this approach include improving the quality of education management, optimizing resources, better decision-making, and the ability to face complex challenges in education in a more systematic way. The research method used is the literature review method or literature review researchers identify, collect, and review relevant scientific works to gain an in-depth understanding of the topic being studied without collecting primary data directly.